2022
DOI: 10.3389/fnins.2021.798823
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Potentials in Women on the Pill: Neural Correlates of Positive and Erotic Stimulus Processing in Oral Contraceptive Users

Abstract: Background/Aims: Exposure toward positive emotional cues with – and without – reproductive significance plays a crucial role in daily life and regarding well-being as well as mental health. While possible adverse effects of oral contraceptive (OC) use on female mental and sexual health are widely discussed, neural processing of positive emotional stimuli has not been systematically investigated in association with OC use. Considering reported effects on mood, well-being and sexual function, and proposed associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 126 publications
(192 reference statements)
1
5
0
Order By: Relevance
“…Earlier research has also indicated reduced SF and erotic stimulus processing in OC users ( Wallwiener et al, 2010 ; Abler et al, 2013 ; Monciunskaite et al, 2019 ). However, our moderation models did not yield significant OC effects, consistent with the mixed results in this field ( Schaffir, 2006 ; Schmidt et al, 2022 ). These inconsistencies highlight the importance of considering psychosexual variables such as SE/SI in sexuality research alongside biological predictors like sex steroid concentration or OC use.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Earlier research has also indicated reduced SF and erotic stimulus processing in OC users ( Wallwiener et al, 2010 ; Abler et al, 2013 ; Monciunskaite et al, 2019 ). However, our moderation models did not yield significant OC effects, consistent with the mixed results in this field ( Schaffir, 2006 ; Schmidt et al, 2022 ). These inconsistencies highlight the importance of considering psychosexual variables such as SE/SI in sexuality research alongside biological predictors like sex steroid concentration or OC use.…”
Section: Discussionsupporting
confidence: 86%
“…This paradigm has proven to be a suitable implicit measure of sexual interest, especially when combined with ERP techniques ( Ciardha and Gormley, 2009 , 2012 ; Munk et al, 2018 , 2020 ) and several studies confirm the usability of Emotional Stroop Paradigms for eliciting ERPs ( Thomas et al, 2007 ; Bertsch et al, 2009 ; Franken et al, 2009 ; Munk et al, 2018 , 2020 ; Imbir et al, 2021 ; Paul et al, 2022 ). Due to the comprehensive nature of the overall project, several emotional stimulus categories were included ( Schmidt et al, 2022 ). However, regarding SE/SI, only the following stimulus categories were considered in the present study: Pictures of scantily dressed erotic couples in intimate poses (couple erotic), pictures of scantily dresses males (male erotic) and females (female erotic) in upright positions, pictures of fully dressed couples (couple neutral) and fully dressed single individuals (person neutral) in neutral poses and neutral facial expressions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations